A Comparison of Online and Face-to-Face Approaches to Teaching Introduction to American Government. Issue 3 (2nd July 2016) - Bolsen, Toby; Evans, Michael; Fleming, Anna McCaghren
ABSTRACT: This article reports results from a large study comparing four different approaches to teaching Introduction to American Government: (1) traditional, a paper textbook with 100% face-to-face lecture-style teaching; (2) breakout, a paper textbook with 50% face-to-face lecture-style teaching and 50% face-to-face small-group breakout discussion sections moderated by graduate students; (3) blended, an interactive online textbook with face-to-face full-class meetings taught with a blend of lecture, discussions, and in-class activities; and (4) online only, an interactive online textbook with (almost) no face-to-face class meetings. We find that the mode of course delivery is significantly related to student academic engagement and performance as well as civic educational outcomes. Although drop rates were higher in the online only condition, students who successfully completed the online course were significantly more likely to express interest in discussing and participating in politics. Furthermore, students in the online only and blended conditions demonstrated significantly higher levels of objective political knowledge relative to students taking the course in a more traditional format. Finally, students enrolled in sections that assigned the interactive online textbook rated their textbook as significantly more beneficial to their learning experiences than did students who used the traditional paper textbook.